2005
DOI: 10.1164/rccm.200506-890oc
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms and Haplotypes of Acid Mammalian Chitinase Are Associated with Bronchial Asthma

Abstract: This newly described association between AMCase polymorphisms and asthma adds further evidence supporting the involvement of AMCase in the development of asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
118
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(125 citation statements)
references
References 28 publications
4
118
3
Order By: Relevance
“…This hypothesis is in agreement with recent studies suggesting that genetic polymorphisms in AMCase, but not ChTRase, are associated with bronchial asthma in Caucasian pediatric populations. 25,26 We have recently shown that, similarly to ChTRase, the chitinase-like protein YKL-40 is up-regulated in BAL and alveolar macrophages from COPD patients, but not asthmatics.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is in agreement with recent studies suggesting that genetic polymorphisms in AMCase, but not ChTRase, are associated with bronchial asthma in Caucasian pediatric populations. 25,26 We have recently shown that, similarly to ChTRase, the chitinase-like protein YKL-40 is up-regulated in BAL and alveolar macrophages from COPD patients, but not asthmatics.…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al (2004) reported that acid mammalian chitinase may be an important mediator of IL13-induced responses in Th2-dominated disorders such as asthma. An association between acid mammalian chitinase polymorphisms and asthma further supports the involvement of acid mammalian chitinase in asthma development (Bierbaum et al, 2005).…”
Section: Introductionmentioning
confidence: 62%
“…Acid mammalian chitinase may also be an important mediator of IL13-induced responses in Th2 disorders, such as asthma (Zhu et al, 2004). Indeed, polymorphisms in acid mammalian chitinase are associated with asthma, further supporting the involvement of acid mammalian chitinase in asthma development (Bierbaum et al, 2005). DEP induces airway hyper-responsiveness as well as Ym mRNA expression, a Th2 cell-biased response by activated macrophages.…”
Section: Innate Immunitymentioning
confidence: 95%